DETERMINAN VARIABEL WORD OF MOUTH (WOM) DAN ISLAMIC BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PROPERTI SYARIAH (THE MATA RESIDENCE KABUPATEN GOWA) - Fadly Yashari Soumena; Nurul Qayyum (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
This research uses a Descriptive Quantitative approach. The data used is primarily using questionnaires and observations. The analysis method used is a multiple linear regression test. The population in this study is all consumers who purchase Sharia housing at The Mata Residence in Pattallassang District, Gowa Regency, while the sample used in this study was 50 respondents. Partially, the results of the study showed that (1) Word of Mouth (WoM) had a positive and significant effect on the decision to purchase Sharia housing at The Mata Residence in Pattallassang District, Gowa Regency. (2) Islamic Brand Image has a positive and significant influence on the decision to purchase Sharia housing The Mata Residence in Pattallassang District, Gowa Regency. (3) Word of Mouth (WoM) and Islamic Brand Image together /simultaneously have a positive and significant effect on the decision to purchase Sharia housing The Mata Residence in Pattallassang District, Gowa Regency. WoM and Islamic brands contribute to the purchase decision, so far the housing of The Mata Residence has no fines or confiscations in case of payment delays. So, in overcoming the problem for house seekers before buying Sharia property, check first because it is feared that the momentum will actually be used by rogue developers who want to get personal benefits or damage the name of Shariah. Consumers must be careful not to let the intentions sharia but instead deceived in the future.